2020
DOI: 10.1177/1099636219900343
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of integrated and non-integrated corrugated core sandwich panels reinforced with weft-knitted fabrics

Abstract: This study deals with free vibration analysis of integrated and non-integrated corrugated core sandwich panels with rectangular core together with free vibration analysis of integrated corrugated core sandwich panels with hat-type and triangle core. Bonding of the core to skin in non-integrated sandwich panels was achieved by resin, while in the integrated sandwich panels that were reinforced with 3-D weft-knitted fabric bonding was achieved using yarns and resin. Results revealed that the integrated structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Assessment of the total reaction forces predicted using the two finite element models is based on evaluating the efficient elastic constant of honeycomb cores. Abedzade Atar et al [ 15 ] Studied free vibration analysis of corrugated core rectangular core sandwich panels.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of the total reaction forces predicted using the two finite element models is based on evaluating the efficient elastic constant of honeycomb cores. Abedzade Atar et al [ 15 ] Studied free vibration analysis of corrugated core rectangular core sandwich panels.…”
Section: Introductionmentioning
confidence: 99%
“…The alternate sequence of 2-ply laminate provides bending resistance in the direction of corrugation. The authors of this paper in their previous article have shown that in the transverse direction of corrugation integrated structure exhibits both higher natural frequency and higher flexural stiffness compared to the non-integrated structure [20]. Additionally, the thickness of the non-integrated samples is more than that of the integrated samples.…”
Section: Comparison Of the Three Methods Of Elastic Constant Determinmentioning
confidence: 78%
“…Stoll CMS-400 (E5) flat weft knitting machine was used to knit the 3-D reinforcement fabric with rectangular cross section for use in integrated sandwich panel. The same machine was also used to knit the conventional 2-D fabrics as the reinforcement of the non-integrated sandwich panel according to Abedzade et al [20]. Figure 1 illustrates the schematic and the actual 3-D knitted fabric.…”
Section: Methodsmentioning
confidence: 99%
“…[62][63][64] Compared to other structural forms of lattice materials, the vibration response of integrated hollow sandwich structures is less studied, which is not favorable to the structure against mechanical vibrations. Abedzade Atar et al 65 investigated the effect of structural topology and core-panel integrity on the vibration of the structure. Modal tests and numerical simulations determined the inherent frequencies of the specimens.…”
Section: Integrated Hollow Core Materialsmentioning
confidence: 99%